The factors influencing the efficiency of drug-coated balloons - Cao, Zheng; Li, Jun; Fang, Zhao; Feierkaiti, Yushanjiang; Zheng, Xiaoxin; Jiang, Xuejun (Frontiers in Cardiovascular Medicine, 2022)
The drug-coated balloon (DCB) is an emerging percutaneous coronary intervention (PCI) device, which delivers drug to the diseased vessel to decrease the rate of vascular stenosis. Recent clinical studies have demonstrated that DCB tends to have both good safety and efficacy profile, leading to extended application indications in clinic, including in-stent restenosis (ISR) for metal stents like the drug-eluting stents (DES), small vascular disease, bifurcation disease, large vascular disease, acute coronary syndrome (ACS), and high bleeding risk. However, some previous clinical data suggested that DCB performed less effectively than DES. No study or review has systematically discussed the improvement strategies for better performance of DCB until now. Drug loss during the process of delivery to the target lesion and inefficient delivery of the coating drug to the diseased vascular wall are two key mechanisms that weaken the efficiency of DCB. This review is the first one to summarize the key influencing factors of DCB efficiency in terms of balloon structure and principles, and then analyzes how these factors caused outcomes in practice based on current clinical trial studies of DCB in treatment of different types of lesions. We also gave some recommendations for improvement of DCB, for the purpose of contribution to a better performance of DCB through improving the design of DCB and combining other factors in clinical practice